Design, synthesis and immunological evaluation of monophosphoryl lipid A derivatives as adjuvants for a RBD-hFc based SARS-CoV-2 vaccine - Su, Shiwei; Chen, Liqing; Yang, Menglan; Liang, Dan; Ke, Bixia; Liu, Zhongqiu; Ke, Changwen; Liao, Guochao; Liu, Liang; Luo, Xiang (MedChemComm, 2023)
Toll-like receptor 4 (TLR4) is a reliable target for the development of vaccine adjuvants. To identify novel TLR4 ligands with improved immunological properties for use as adjuvants for a RBD-hFc based SARS-CoV-2 vaccine, herein, natural E. coli monophosphoryl lipid A (MPLA) and nine of its derivatives were designed and synthesized. Immunological evaluation showed that compounds 1 , 3 , 5 and 7 exhibited comparative or better adjuvant activity than clinically used Al adjuvants, and are expected to be a promising platform for the development of new adjuvants used for a RBD-hFc based SARS-CoV-2 vaccine. Preliminary structure-activity relationship analysis of the MPLA derivatives showed that the replacement of the functional groups at the C-1, C-4′ or C-6′ position of E. coli MPLA has an effect on its biological activity. In addition, we found that the combination of MPLA and Al was feasible for immunotherapy and could further enhance immune responses, providing a new direction toward the immunological enhancement of RBD-hFc based SARS-CoV-2 vaccines. MPLA derivatives are expected to be a promising platform for the development of new adjuvants used for a RBD-hFc based SARS-CoV-2 vaccine.